DEVELOPMENT OF CERAMIC MICROFILTRATION SUPPORT FROM MOROCCAN SAHARA CLAY - NOURLYAQUIN EL QACEMI; NABIL SAFFAJ; RACHID MAMOUNI; NOURREDINE EL BARAKA; HAMID ZIDOUH; MOHAMED AIT BAIH; ABDELATIF AKNIFLI (Journal of Engineering Studies and Research)
The new ceramic microfiltration support prepared from Moroccan clay (Laayoune region, South of Morocco) is reported in this paper. To optimize the support elaboration conditions, the powder clay is mixed with organic additives and water. The formed paste is shaped by using an extrusion processing and then sintered at 950 °C. The ceramic supports present a porosity and mechanical strength of 44 % and 12MPa respectively. The layer filtration deposition has been carried out by the slip casting method, in order to test its operation in textile effluents treatment.